Credit Needs of Rice Farmer-Households in Tayabas City, Quezon, 2015-2016 (Philippine Journal of Agricultural Economics, 2017)
Credit has provided a way to meet the requirements for rice production and household needs especially during the period when farmers wait for their harvest. Further examination on timing of funds of rice farmers is necessary so that their demand for credit can be sufficiently met. The study aimed to evaluate the credit needs of rice farmer-households in Tayabas City located in Quezon Province, Philippines. This was done by interviewing 90 randomly selected rice farmers with an aid of pre-tested questionnaire. The households' credit needs were assessed using funds flow analysis. Households' credit needs are the amount of deficit incurred from spending all expenditures. It was found out that farmers' demand for credit was at maximum during the months of December and June since these months were the start of cropping periods. Thus, they acquired necessary inputs and paid laborers. On the other hand, no demand for credit was observed during the months of March, April, August, September, and October. This was due to significant amount of income earned from rice farming and other farms. The findings of the study provide some implications on timing of credit distribution and monitoring of clients' funds flow. Furthermore, sufficient livelihood programs must be provided by the government to offset capital insufficiency especially during period of waiting for harvest.